The effect of different type of additives on friction and wear of MNR grease - Wan Yusof, Wan Fairuz (2023)
Grease typically has a base of mineral or synthetic oil, a thickener, additives, and fillers. The tribological performance of grease depends on the viscosity of the base oil and the type and concentration of thickening agent used. Grease lubricants are used in many different parts of automobiles, including gears, cams, sealed ball bearings, and others. Having to use more energy to overcome vehicle friction is wasteful. Power consumption can be drastically cut if frictional losses are minimised, making the components more effective. Grease lubrication helps keep surfaces apart, reducing friction and wear for increased durability. Prepared by sonicating the grease supplied by MNR Multitech Sdn Bhd using an ultrasonic homogenizer, the produced greases had a 10% concentration of additive nanoparticles of varying types mixed in. To put it simply, MNR is a grease that has no additives added to it. Molybdenum disulfide (MoS2), lithium complex grease (LCG), and potassium (MNR + K) are some of the other additives that have been introduced (K). Tribological tests were conducted using a 4-Ball Tester in accordance with the American Society for Testing and Materials (ASTM) standards D 2266 for Wear Preventive Characteristics of Lubricating Grease (Four-Ball Method) and 2596 for measurement of Extreme-Pressure Properties of Lubricating Grease (Four-Ball Method). The testing results show that the addition of MoS2 additives to MNR base grease can increase its friction and wear qualities by 52% and 68%, respectively. Extreme pressure testing revealed that MNR + MoS2 grease reduced severe adhesive wear and increased load carrying capability by nearly double that of MNR grease, from 618.03 N to 784.8 N. As a result, the load-carrying capacity and the friction coefficient have both been drastically increased thanks to the additive's use in bearing.